Pengaruh Lingkungan Terhadap Kepekaan Sistem Indra Pada Manusia - Nazwa Rumaysa Aulia; Irginia Sofianthi; Oviantika Dwi Safitri; Syafira Ayu Damayanti; Nadia Vivin Melani; Chika Adelia Saftri; Naswa Lathifah Ainur Risma; Liss Dyah Dewi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The human sensory system, which includes sigt, hearing, smell, taste, and touch, is greatly influenced by environmental factors. This study examines how elements such as light, temperature, and noise can alter sensory sensivity, based on physiological and physiological studies. The results show that extreme environments can decrease sensory sensitivity through adaptation or damage, while balanced environments increase it. Pratical implications include better environmental design for human health. The research method use in this study is a qualitative descriptive method with a literature study approach. This study was conducted to analyze the influence of the environment on the sensitivity of the sensory system in humans. The data used in this study were obtained from various secondary sources, such as scientific journals, reference books, and relevant research reports.